Lecture Notes in Mathematics 2006
DOI: 10.1007/b128444
|View full text |Cite
|
Sign up to set email alerts
|

The Lace Expansion and its Applications

Abstract: ii The Lace Expansion and its ApplicationsThe Lace Expansion and its Applications iii Preface Several superficially simple mathematical models, such as the self-avoiding walk and percolation, are paradigms for the study of critical phenomena in statistical mechanics. Although these models have been studied by mathematicians for about half a century, exciting new developments continue to occur and the subject is flourishing. Much progress has been made, but it remains a major challenge for mathematical physics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 192 publications
(461 reference statements)
0
2
0
Order By: Relevance
“…Besides, there is a variety of excellent books and survey articles on random walks or directly related to random walks by Bingham [95,96], Bladt and Nielsen [97], Blanchard and Volchenkov [21], Brémaud [22], Fayolle, Iasnogorodski, and Malyshev [15], Foss, Korshunov, and Zachary [98], Fujie and Zhang [23], Gut [99], Hildebrand [16], Iksanov [100], Lawler [101], Redner [79], Shi [25], Slade [102], Takács [2], Telcs [103], and Wijesundera, Halgamuge, and Nanayakkara [104].…”
Section: Related Literaturementioning
confidence: 99%
“…Besides, there is a variety of excellent books and survey articles on random walks or directly related to random walks by Bingham [95,96], Bladt and Nielsen [97], Blanchard and Volchenkov [21], Brémaud [22], Fayolle, Iasnogorodski, and Malyshev [15], Foss, Korshunov, and Zachary [98], Fujie and Zhang [23], Gut [99], Hildebrand [16], Iksanov [100], Lawler [101], Redner [79], Shi [25], Slade [102], Takács [2], Telcs [103], and Wijesundera, Halgamuge, and Nanayakkara [104].…”
Section: Related Literaturementioning
confidence: 99%
“…The series expansion for μ was placed on a much firmer footing by Hara and Slade using the lace expansion [7]. The lace expansion is a powerful technique for exploring the properties of the self-avoiding walk in dimensions d > 4; we refer the reader to [8] for a recent introduction. Hara and Slade showed that the connective constant μ has an asymptotic expansion in integer powers of 1/(2d) to all orders, with all the coefficients taking integer values.…”
Section: Introductionmentioning
confidence: 99%